Hemolivia and hepatozoon: haemogregarines with tangled evolutionary relationships - Kvičerová, Jana; Hypša, Václav; Dvořáková, Nela; Mikulíček, Peter; Jandzik, David; Gardner, Michael George; Javanbakht, Hossein; Tiar, Ghoulem; Siroký, Pavel (Protist, 2014)
The generic name Hemolivia has been used for haemogregarines characterized by morphological and biological features. The few molecular studies, focused on other haemogregarine genera but involving Hemolivia samples, indicated its close relationship to the genus Hepatozoon. Here we analyze molecular data for Hemolivia from a broad geographic area and host spectrum and provide detailed morphological documentation of the included samples. Based on molecular analyses in context of other haemogregarines, we demonstrate that several sequences deposited in GenBank from isolates described as Hepatozoon belong to the Hemolivia cluster. This illustrates the overall difficulty with recognizing Hemolivia and Hepatozoon without sufficient morphological and molecular information. The close proximity of both genera is also reflected in uncertainty about their precise phylogeny when using 18S rDNA. They cluster with almost identical likelihood either as two sister taxa or as monophyletic Hemolivia within paraphyletic Hepatozoon. However, regardless of these difficulties, the results presented here provide a reliable background for the unequivocal placement of new samples into the Hemolivia/ Hepatozoon complex.
Keywords: RNA, Ribosomal, 18S; ribozomální DNA; DNA, Ribosomal; Coccidia; shluková analýza; Molecular Sequence Data; phylogeny.; haemogregarines; Hemolivia; Phylogeny; molekulární sekvence - údaje; DNA, Protozoan; host specificity; protozoální DNA; RNA ribozomální 18S; Hepatozoon; Sequence Analysis, DNA; Apicomplexa; sekvenční analýza DNA; Cluster Analysis; mikroskopie; fylogeneze; Microscopy